Quality of life in liver transplant recipients during the Corona virus disease 19 pandemic: A multicentre study. (2nd April 2022) - Gitto, Stefano; Golfieri, Lucia; Mannelli, Nicolò; Tamè, Maria Rosa; Lopez, Ivo; Ceccato, Roberta; Montanari, Stanislao; Falcini, Margherita; Vitale, Giovanni; De Maria, Nicola; Presti, Danilo Lo; Marzi, Luca; et al.
Abstract: Background: Liver transplant recipients require specific clinical and psychosocial attention given their frailty. Main aim of the study was to assess the quality of life after liver transplant during the current pandemic. Methods: This multicentre study was conducted in clinically stable, liver transplanted patients. Enrollment opened in June and finished in September 2021. Patients completed a survey including lifestyle data, quality of life (Short Form health survey), sport, employment, diet. To examine the correlations, we calculated Pearson coefficients while to compare subgroups, independent samples t ‐tests and ANOVAs. To detect the predictors of impaired quality of life, we used multivariable logistic regression analysis. Results: We analysed data from 511 patients observing significant associations between quality of life's physical score and both age and adherence to Mediterranean diet (p < .01). A significant negative correlation was observed between mental score and the sedentary activity (p < .05). Female patients scored significantly lower than males in physical and mental score. At multivariate analysis, females were 1.65 times more likely to report impaired physical score than males. Occupation and physical activity presented significant positive relation with quality of life. Adherence to Mediterranean diet was another relevant predictor. Regarding mental score, female patients were 1.78 times more likely to show impaired mental score in comparison with males. Sedentary activity and adherence to Mediterranean diet were further noteworthy predictors. Conclusions: Females and subjects with sedentary lifestyle or work inactive seem to show the worst quality of life and both physical activity and Mediterranean diet might be helpful to improve it.